2010
DOI: 10.1042/bst0381458
|View full text |Cite
|
Sign up to set email alerts
|

Endolysosomal calcium regulation and disease

Abstract: Until recently, the mechanisms that regulate endolysosomal calcium homoeostasis were poorly understood. The discovery of the molecular target of NAADP (nicotinic acid-adenine dinucleotide phosphate) as the two-pore channels resident in the endolysosomal system has highlighted this compartment as an important calcium store. The recent findings that dysfunctional NAADP release leads to defective endocytic function which in turn results in secondary lipid accumulation in the lysosomal storage disease Niemann-Pick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 60 publications
(99 reference statements)
0
47
1
1
Order By: Relevance
“…Even when a primary defi ciency in a lysosomal glycohydrolase, activator protein, or saposin directly involved in the degradation of GM2 or GM3 ( 52 ) is not present, the accumulation of GM2/GM3 appears to occur, at least in part, in the endosomal/lysosomal system ( 26,29,30,34,53 ) and/or in lipid rafts ( 24,27,33 ). As well as for defi ciencies in catabolic proteins not directly involved in degradation of these gangliosides, defects in traffi cking of gangliosides from endosomes to the Golgi apparatus ( 53,54 ) or from late endosomes to lysosomes ( 55,56 ) also observed in some lysosomal storage diseases can produce similar accumulation. In chronic diseases, such ganglioside accumulation is typically detected in neurons ( 29,30,34,57 ) and, in some cases, in activated microglia ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even when a primary defi ciency in a lysosomal glycohydrolase, activator protein, or saposin directly involved in the degradation of GM2 or GM3 ( 52 ) is not present, the accumulation of GM2/GM3 appears to occur, at least in part, in the endosomal/lysosomal system ( 26,29,30,34,53 ) and/or in lipid rafts ( 24,27,33 ). As well as for defi ciencies in catabolic proteins not directly involved in degradation of these gangliosides, defects in traffi cking of gangliosides from endosomes to the Golgi apparatus ( 53,54 ) or from late endosomes to lysosomes ( 55,56 ) also observed in some lysosomal storage diseases can produce similar accumulation. In chronic diseases, such ganglioside accumulation is typically detected in neurons ( 29,30,34,57 ) and, in some cases, in activated microglia ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ned19-induced effects on trafficking in wild type cells may indicate a physiological role for NAADP-mediated Ca 2+ release in endolysosomal physiology. Such defects are often observed in lysosomal storage disease phenotypes, and recently lysosomal Ca 2+ dysregulation has been presented as a causal factor in these diseases [75]. Particularly interesting recent findings are that cells from Niemann-Pick type C patients contain lysosomes with low Ca 2+ storage and defective NAADP-mediated Ca 2+ release [45].…”
Section: Local Ca 2+ Release In the Endolysosomal System And Its Pathmentioning
confidence: 99%
“…Particularly interesting recent findings are that cells from Niemann-Pick type C patients contain lysosomes with low Ca 2+ storage and defective NAADP-mediated Ca 2+ release [45]. Conversely, in cells from patients with mucolipidosis IV which lack functional mucolipin 1 channels, NAADP-evoked Ca 2+ release is enhanced and associated with enlarged lysosomes [75].…”
Section: Local Ca 2+ Release In the Endolysosomal System And Its Pathmentioning
confidence: 99%
“…9). In response to different physiological and pathological stimulations, lysosomal Ca 2ϩ can be mobilized or released to mediate molecular trafficking or recycling and to control vesicular fusion events associated with lysosomes (15,19,22). Recently, this lysosomal Ca 2ϩ release is found to be mediated by transient receptor potential-mucolipin 1 (TRP-ML1) channel, a…”
mentioning
confidence: 99%
“…signaling lysosomes; transient receptor potential channel; Ca 2ϩ mobilization; programmed cell death LYSOSOME-MEDIATED SIGNALING is a novel mechanism that regulates intracellular Ca 2ϩ levels in a variety of mammalian cells (15,18). It has been reported that lysosomes contain high levels of Ca 2ϩ , which serve as an important intracellular Ca 2ϩ store as does the sarcoplasmic reticulum (SR; Ref.…”
mentioning
confidence: 99%